Impact of chitosan composites and chitosan nanoparticle composites on various drug delivery systems: a review - Elgadir, M.Abd; Uddin, Md. Salim; Ferdosh, Sahena; Adam, Aishah; Khan Chowdhury, Ahmed Jalal; Sarker, Md. Zaidul Islam (National Laboratories of Foods and Drugs, 2015)
Chitosan is a promising biopolymer for drug delivery systems. Because of its beneficial properties, chitosan is widely used in biomedical and pharmaceutical fields. In this review, we summarize the physicochemical and drug delivery properties of chitosan, selected studies on utilization of chitosan and chitosan-based nanoparticle composites in various drug delivery systems, and selected studies on the application of chitosan films in both drug delivery and wound healing. Chitosan is considered the most important polysaccharide for various drug delivery purposes because of its cationic character and primary amino groups, which are responsible for its many properties such as mucoadhesion, controlled drug release, transfection, in situ gelation, and efflux pump inhibitory properties and permeation enhancement. This review can enhance our understanding of drug delivery systems particularly in cases where chitosan drug-loaded nanoparticles are applied.